Ecological agriculture utilizes system based on slope cropland grows combination - LANG FENGLIAN; ZHANG LEILEI; WU BOZHI; ZHANG XIAOYUN; WU KAIXIAN; LI YONGXIAN (2018)
The utility model provides an ecological agriculture utilizes system based on slope cropland grows combination, including slope cropland, water circulation system, irrigation system, the sensors monitor system, the gate valve switching system, photovoltaic power generation system and intelligence control system, slope cropland divides light energy acquisition unit into from top of slope to toe, grain crop plants the unit, raise and use and economic crop water insurance policy unit, aquaculture unit I, grain crop plants the unit, raise and use and economic crop water insurance policy unit and aquaculture unit II, photovoltaic power generation system is become by a plurality of solar cell panel set, water circulation system is by aquaculture unit I, aquaculture unit II, the second pump body,ascension pipe and dirty pipeline are formed, this system is one kind and is suitable for the ecological agriculture system that slope cropland grew the combination, can effectively solve slope cropland arid water -deficient